In‐Fjord Substitution in Expanded Helicenes: Effects of the Insert on the Inversion Barrier and Helical Pitch. Issue 53 (13th August 2021) - Suárez‐Pantiga, Samuel; Redero, Pablo; Aniban, Xaiza; Simon, Martin; Golz, Christopher; Mata, Ricardo A.; Alcarazo, Manuel
Abstract: A series of expanded helicenes of different sizes and shapes incorporating phenyl‐ and biphenyl‐substituents at the deepest part of their fjord have been synthesized via sequential Au‐catalyzed hydroarylation of appropriately designed diynes, and their racemization barriers have been calculated employing electronic structure methods. These show that the overall profile of the inversions (energies, number of transition states and intermediates, and their relative position) is intensively affected by the interplay of steric and attractive London dispersion interactions. Hence, in‐fjord substitution constitutes an additional tool to handle the mechanical properties in helicenes of uncommonly large diameter. The photochemical characterization of the newly prepared helical structures is also reported. Abstract : Deep in‐fjord substitution is presented as a new tool to control the mechanical properties of expanded helicenes. The syntheses of a series of these compounds containing internal inserts is described and their overall inversion profile is calculated. Interestingly, the interplay between steric and dispersion interactions play a major role in shape of the inversion profiles (energies, number of transition states and intermediates).